A Scoping Review of the Psychological and Emotional Impact of the COVID-19 Pandemic on Children and Young People. (January 2023) - Jones, K.; Mallon, Sharon; Schnitzler, Katy
Background: The COVID-19 pandemic has resulted in many changes to the lives of children and young people. Our aim is to explore the impact of the pandemic on the mental health of children and young people (ages 5–21). Methods: The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines was used to report the findings of this rapid review. Results: Children and young people are potentially very vulnerable to the emotional impact of traumatic events that disrupt their daily lives. Key areas of concern include: Death Anxiety and Fear of Infection; lack of social interaction and loss of routine. Conclusions: Despite some early and responsive studies, the evidence base for pandemic impact on children and young people is very limited. Such evidence is urgently needed if adequate and responsive services, that can mitigate the long-term impact of the pandemic for children and young people can be established.